Risk management strategy for iB KPR financing in Islamic bank - Rahmadayana, Rizka Dwi; Harahap, Muhammad Ikhsan; Irham, Mawaddah (LPMP Imperium, 2024)
This research analyzes the risk management strategies employed in the iB Syariah Tapak KPR financing to understand how the bank aims to minimize the risks associated with high non-performing financing. The study uses a descriptive qualitative research methodology to gather data through various techniques, including observation, interviews, and case studies for primary data. In contrast, secondary data is sourced from literature such as books and journals. The findings reveal that the rise in non-performing financing is attributed to several factors, including economic conditions, the capacity of debtors, force majeure events, and the character of customers. PT Bank Sumut KCP Syariah Karya has developed a comprehensive risk management strategy in response to these challenges. This strategy includes blocking installment funds for 12 months, offering buy-back guarantees, and providing customer insurance to mitigate risks. Public interest statements As banks adopt these strategies to improve customer satisfaction, the public can expect increased competition in the banking sector. This competition may lead to better services, lower fees, and more innovative products, benefiting consumers. Article Info: Received 6/10/2024 | Revised: 9/27/2024 | Accepted: 9/23/2024 |Online First 9/27/2024